Fatores associados aos gastos com medicamentos utilizados por aposentados e pensionistas idosos em Belo Horizonte/MG - Marina Guimaraes Lima (2008)
Drug expenditures of the elderly people have been increasing quickly because of their epidemiological profile, characterized by chronic degenerative diseases. In Brazil, theres little available information in the literature on drug spending among the elderly people. The aim of this study was analyzing drug spending among elderly people in Belo Horizonte, Minas Gerais. This was a cost study based on informationfrom a populational survey, with a representative sample of retired people aged 60 years or more. Private and public expenditures on drugs used by elders in last 15 days were calculated. Descriptive statistics (mean, median, and standard deviation) were obtained for spending values. An analysis was performed to study association between drug spending and selected variables using Tobit regression, at a 5% significance level. The final sample was composed by 667 individuals. The private mean drug cost was R$ 122,97 (US$ 38,91) and the public mean drug cost was R$13,97 (US$ 4,42). The therapeutic groups that represent the main part of private and public drug costs were: Cardiovascular System, Nervous System and Alimentary Tract and Metabolism. Considering registration drug categories, the brand drugs composed the main part of private and public costs. Non-essential and inappropriate medicines for elders represented substantial parts of expenditures. The variablesassociated (p<0,05) with private drug spending were: higher level of schooling, number of diseases, use of private health plan, use of higher number of medicines, proportion of non-essential medicines, proportion of inappropriate medicines, proportion of brand medicines and proportion of new medicines. The substitution of generics for brand medicines in elders reduced potentially the private mean drug cost in 21,8%. The results of this study can supply subsidies to health care planningrelated to drug use by individuals aged 60 years or more, supporting policies to improve health conditions of Brazilian elderly population.